Scams issues among elderly: a conceptual paper - Saifuddin, Nurul Faqihah; Musa, Balqis; Zakaria, Nurin Sofiya; Othman, Nur Farhana; Putera, Andito Dwicahyo; Kunasekaran, Puvaneswaran; Rosnon, Mohd Roslan; Abdul Razak, Muhammad Afiq; Ibrahim, Rahimah (Human Resources Management Academic Research Society (HRMARS), 2024)
This study aims to identify and analyse the key factors of scams among the elderly. In the context of rapid technological advancement, the elderly are particularly vulnerable to scams due to their limited technological knowledge and inherent trust in others which threaten their well-being. Existing literature highlights that elderly are frequent targets of online scams due to declining cognitive abilities and social isolation. The analysis encompasses a comprehensive review of relevant studies and demographic data to explore the factors contributing to scams targeting the elderly. This paper identifies four factors that make the elderly expose to scams which are (i) cognitive decline; (ii) social isolation; (iii) non-technologies savvy and; (iv) financial stability. There are five types of scams that target older people which are (i) government impersonation scams; (ii) sweepstakes and lottery scams; (iii) robocalls and phone scams; (iv) computer tech support scams and; (v) grandparents’ scams. This study shows the impact of scams on the (i) financial and (ii) emotional security of the elderly. This paper provides valuable insights for readers on the mechanisms of scams targeting the elderly and offers a foundation for developing effective preventive measures and educational initiatives to protect this vulnerable population.